(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Ammomum subulatum is a perennial plant cultivated in swampy places in Bengal, Sikkim, Assam and Tamil Nadu. Plant bears fruit having numerous seeds which are traditionally used in spice. Fruits are used as stimulant, aromatic, stomachic, aphrodisiac, in infection of teeth and gums. The present study is an attempt to explore the anti-inflammatory activity of ethanolic and aqueous extract of fruit of Ammomum subulatum. Dose of 100 mg/ml and 200 mg/ml of ethanolic and aqueous extract were evaluated for their anti-inflammatory activity against carrageenan induced paw edema in rat. Both the extracts were able to show anti-inflammatory activity in dose dependant manner as compared with standard drug Diclofenac sodium 100 mg/ml. The data were found statistically significant by using one way ANOVA (P< 0.001).